2018
DOI: 10.12717/dr.2018.22.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Distances in Two Gracilaria Species (Gracilariaceae, Rhodophyta) Identified by PCR Technique

Abstract: Genomic DNA was isolated from the Gracilaria vermiculophylla (GRV) and G. chorda (GRC) from Jangheung located in the southern sea of the Korean Peninsula, respectively and we performed clustering analyses, DNA polymorphisms and the genetic differences. The seven selected primers OPC-01, OPA-04, OPA-05, OPD-07, OPD-08, OPB-10, and OPD-16 generated average bandsharing (BS) value, the genetic distance and dendrogram. The size of DNA bands varies from 90 bp to 2,400 bp. The average BS value was 0.859±0.004 within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Sixty-one bands varying from 200 bp to 1,900 bp were explicitly calculated in the ectoparasitic caligid (Lepeophtheirus salmonis) (Dixon et al, 2004). The amounts of the DNA FRs also fluctuated broadly, from 90 to 2,400 bp in Gracilaria vermiculophylla and G. chorda (Kim & Yoon, 2018). Yoon (2018) also reported that the greater FR sizes (>1,100 bp) are not detected in the razor shellfish (Solen corneus) bi-group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-one bands varying from 200 bp to 1,900 bp were explicitly calculated in the ectoparasitic caligid (Lepeophtheirus salmonis) (Dixon et al, 2004). The amounts of the DNA FRs also fluctuated broadly, from 90 to 2,400 bp in Gracilaria vermiculophylla and G. chorda (Kim & Yoon, 2018). Yoon (2018) also reported that the greater FR sizes (>1,100 bp) are not detected in the razor shellfish (Solen corneus) bi-group.…”
Section: Resultsmentioning
confidence: 99%
“…The aptitude of ON-polymers augmented DNAs to determine unique markers for line, strain, species, genus, and group proof of identity in life entities (Koh et al, 1999;Esselman et al, 2000;Huang et al, 2000;Kim et al, 2000;Dixon et al, 2004;García et al, 2004;Araneda et al, 2005;Yamazaki et al, 2005;Yan et al, 2005;Gelin & Souty-Grosset, 2006;Godhe et al, 2006;Kim et al, 2006;Yoon & Kim, 2010;Kang & Yoon, 2013;Oh & Yoon, 2014;Kim & Yoon, 2018) has also been well approved. Great point of an important GD between two Scapharca subcrenata groups showed this research process is one of the most appropriate apparatuses for biotechnological DNA studies on entities and units of other life beings (Koh et al, 1999;Zhou et al, 2000;Kim & Choi, 2003;Dixon et al, 2004;Liu et al, 2004;Araneda et al, 2005;Godhe et al, 2006;Yoon, 2019;Yoon & Kim, 2010;Kang & Yoon, 2013;Yoon, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…DNA FM scales varied from 50 bp to 1,600 bp. It has been reported that seven primers generated the scales of the DNA FMs also varied wildly, from 90 to 2,400 bp from the G. vermiculophylla (GRV) and G. chorda (GRC) ( Kim & Yoon, 2018 ). Group-related PCR FMs were identified in the Oujiang color carp ( Wang & Li, 2004 ) and the F 1 hybrids of masu salmon Oncorhynchus masou masou and amago salmon O. m. ishikawae ( Yamazaki et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…The particular markers definite to breed, species, genus or geographical group have been engaged in the identification of parties, species and populations and genetic diagnostics ( Archak et al, 2003 ; Nagarajan et al, 2006 ; Yoon et al, 2006 ; Kim & Yoon, 2018 ; Yoon, 2019a ). So far, specific fragments (FMs) created by PCR by means of primers were deliberated to be a trustworthy method for discovering DNA relationship between organisms ( Eujayl et al, 1998 ; Almeida et al, 2003 ; Archak et al., 2003 ; Liu & Cordes, 2004 ; Wang & Li, 2004 ; Wasko et al, 2004 ; Bernardet et al, 2005 ; Yamazaki et al, 2005 ; Yue & Orban, 2005 ; Nagarajan et al, 2006 ; Yoon et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive genetic markers specific to breeds, species, genera, and/or geographical populations have been used to identify and distinguish individuals, populations, and hybrid pedigrees based on molecular genetic analysis ( Callejas & Ochando, 1998 ; Mamuris et al, 1999 ; Adams, 2000 ; Bartish et al, 2000 ; Kim et al, 2000 ; Klinbunga et al, 2000b ; McCormack et al, 2000 ; Nebauer et al, 2000 ; Nozaki et al, 2000 ; Chenyambuga et al., 2004 ; Kim et al, 2006 ; Yoon & Kim, 2010 ; Hur et al, 2012 ; Kim & Yoon, 2018 ). Polymerase chain reaction (PCR) techniques have been used in mariculture and aquaculture to determine the genetic distances (GDs) between teleost species and/or invertebrates as well as geographic distribution ( Tassanakajon et al, 1998 ; Huang et al, 2000 ; Klinbunga et al, 2000a ; Zhou et al, 2000 ; Yoon & Park, 2002 ; Kim et al, 2004 ; Park et al, 2005 ; Song & Yoon, 2013 ; Oh & Yoon, 2014 ; Yoon, 2019 ).…”
Section: Introductionmentioning
confidence: 99%